2021
DOI: 10.35848/1882-0786/abe3db
|View full text |Cite
|
Sign up to set email alerts
|

Deep-learning-based semantic image segmentation of graphene field-effect transistors

Abstract: Large-scale graphene films are available, which enables the integration of graphene field-effect transistor (G-FET) arrays on chips. However, the transfer characteristics are not identical but diverse over the array. Optical microscopy is widely used to inspect G-FETs, but quantitative evaluation of the optical images is challenging as they are not classified. Here, we implemented a deep-learning-based semantic image segmentation algorithm. Through a neural network, every pixel was assigned to graphene, electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Recently, label-free methods using field-effect transistors (FETs) [8], surface plasmon resonance [9], and quartz crystal microbalance [10] have been used to detect CRP. In particular, great progress has been made in designing and fabricating FETs using nanomaterials, including Si nanowires [8,11,12], carbon nanotubes [13], and graphene [14][15][16], leading to a sensitive and rapid analysis with miniaturized and integrated sensor platforms [17,18].…”
Section: ◀ Significance ▶mentioning
confidence: 99%
“…Recently, label-free methods using field-effect transistors (FETs) [8], surface plasmon resonance [9], and quartz crystal microbalance [10] have been used to detect CRP. In particular, great progress has been made in designing and fabricating FETs using nanomaterials, including Si nanowires [8,11,12], carbon nanotubes [13], and graphene [14][15][16], leading to a sensitive and rapid analysis with miniaturized and integrated sensor platforms [17,18].…”
Section: ◀ Significance ▶mentioning
confidence: 99%
“…These variations in the transfer curves may be attributed to the graphene tearing, PMMA residue on the graphene, and the impurity charge from the substrate. We previously reported that graphene tearing increases the resistance and decreases the transconductance [22]. It was also reported that both the PMMA residue and SiO 2 substrate have a p-doping effect on graphene [23][24][25].…”
Section: Transfer Curve Variability and Drifts Of Transfer Curvesmentioning
confidence: 95%
“…As highly sensitive sensor devices, transistor-based biochemical sensors have great potential when combined with artificial intelligence (AI). Using machine learning (ML) methods to design devices and quantitatively analyze biological signals measured by transistor-based biochemical sensors may greatly improve detection accuracy and efficiency [ 20 , 21 , 22 , 23 , 24 ]. These developments will help transistor-based biochemical sensors pave the way for the next generation of point-of-care testing [ 25 ].…”
Section: Introductionmentioning
confidence: 99%